2023
DOI: 10.2147/cia.s397614
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Systemic Immune-Inflammation Index and NT-proBNP in Patients with Acute ST-Elevation Myocardial Infarction

Abstract: Objective Our aim was to assess systemic immune-inflammation index (SII) and NT-proBNP value either in singly or in combination to predict acute ST-elevation myocardial infarction (STEMI) patient prognosis. Methods Analyzed retrospectively the clinical features and laboratory data of STEMI confirmed patients in our hospital from January to December 2020. The levels of SII and NT-proBNP were detected. The Kaplan-Meier approach and Spearman’s rank correlation coefficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Previous studies have highlighted the importance of inflammation in AMI in both human and animals. 33 , 34 , 35 , 36 Hypoalbuminaemia is a known marker of inflammation. 37 In the present study, patients with LVA exhibited lower level of ALB than those without LVA, suggesting that inflammation may play a crucial role in this association.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have highlighted the importance of inflammation in AMI in both human and animals. 33 , 34 , 35 , 36 Hypoalbuminaemia is a known marker of inflammation. 37 In the present study, patients with LVA exhibited lower level of ALB than those without LVA, suggesting that inflammation may play a crucial role in this association.…”
Section: Discussionmentioning
confidence: 99%
“…Its prohormone, the N-terminal fragment of the brain-type natriuretic peptide (NT-proBNP), has been found to be correlated to SII [ 40 ]. Moreover, SII and NT-proBNP represented independent determinants of clinical prognosis in acute STEMI patients when considering a composite endpoint (including all-cause mortality, re-hospitalization, nonfatal myocardial infarction, acute heart failure, and non-fatal stroke), and they were positively correlated [ 41 ]. Thus, confounding variables (e.g., creatinine and BNP levels) may alter the association of inflammatory parameters with the outcome in question and should always be considered in the statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The study investigated the association between SII and system inflammation response index (SIRI) with all-cause mortality and cardiovascular mortality in America over a 20-year follow-up period [27]. Zhu Y-confirmed that SII was an independent indicator of clinical prognosis in acute ST-elevation myocardial infarction (STEMI) patients [28]. The Dongfeng-Tongji cohort study in Chinese suggested SII may serve as a useful marker to elucidate the role of the interaction of thrombocytosis, inflammation and immunity in the development of stroke and coronary heart disease (CHD) in the middle-aged and elderly [29].…”
Section: Plos Onementioning
confidence: 94%